2017
DOI: 10.1021/acs.jafc.7b02080
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Study of the Interactions between Ellagitannins and Oxygen during Oak Wood Aging

Abstract: During the aging of red wine in oak wood barrels, or in alternative aging systems, interactions between the compounds released from wood, the compounds of the wine, and oxygen can take place. The main objective of the present work was to study oxygen-ellagitannin interactions by monitoring their levels in three model systems, all containing the same amounts of French oak chips and differing only in the oxygen content: total absence, only the oxygen released from the chips, and air-saturated (model systems F, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Wood composition depends not only on species but also many other factors such as silvicultural, geographic origin and cooperage processing, which affect the extractable fraction [5,13,23,35]. Ellagitannins are transferred to the wine during aging, contributing to sensations of bitterness and astringency [36][37][38] and behaving as antioxidants due to their capacity to consume oxygen [39,40]. Moreover, ellagitannins directly affect wine color via reactions with anthocyanins forming red orange anthocyanin-ellagitannin complexes but are much more stable over time than free anthocyanins [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Wood composition depends not only on species but also many other factors such as silvicultural, geographic origin and cooperage processing, which affect the extractable fraction [5,13,23,35]. Ellagitannins are transferred to the wine during aging, contributing to sensations of bitterness and astringency [36][37][38] and behaving as antioxidants due to their capacity to consume oxygen [39,40]. Moreover, ellagitannins directly affect wine color via reactions with anthocyanins forming red orange anthocyanin-ellagitannin complexes but are much more stable over time than free anthocyanins [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that, when oak chips were flooded with wine, they would provide 0.135 mg of oxygen per gram of oak chips [14]. In wine aging processes, the oxygen contained in alternative products (oak chips, staves, cubes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In oak wood, these compounds are responsible for its hardness and the avoidance of microbiological alterations (Prida, 2002). During wine ageing, they behave as antioxidants thanks to their great ability to consume oxygen (Navarro et al, 2016, García-Estévez et al, 2017. In addition, they accelerate anthocyanin and tannin condensation, which promotes wine flavanol polymerization (flavanoellagitannins) (Cadahía et al, 2008).…”
Section: Introductionmentioning
confidence: 99%